The 18th ICGG in Milan, Italy, hosted by Politecnico di Milano (diségno, 2019)
The 18th International Conference on Geometry and Graphics was held from August 3 – 7, 2018 in Milan, Italy [1].The host institution was the Politecnico di Milano, at the Milano Leonardo Campus. There were many signifcant and unique occurrences which this review will attempt to highlight. (read more)